Teachers and cyberbullying: Interventions, workarounds and frustrations. Issue 2 (15th March 2022) - Thompson, Roberta
ABSTRACT: Cyberbullying is a serious social problem with negative health and wellbeing consequences for young people. Teachers have an important role to play in intervention activities because they are often first responders to cyberbullying events. This paper presents 10 teachers' workarounds to cyberbullying intervention. The vignettes drawn from interview data show teachers recognise cyberbullying as a significant concern for young people. However, in their reporting, there is no uniform approach taken. Instead, each teacher describes a unique set of practices for cyberbullying intervention that are not always aligned to intervention frameworks. While a mix of factors determines their uptake of recommended interventions, the key to each teacher's workaround is the level of frustration, annoyance and worry they experienced in relation to cyberbullying. The research demonstrates intervention frameworks need to rethink the role teachers play in cyberbullying intervention, provide greater support and guidance for managing student distress in relation to cyberbullying, and address the frustration experienced by teachers in relation to their intervention responsibilities.